A Green Metal–Organic Framework‐Cyclodextrin MOF: A Novel Multifunctional Material Based Triboelectric Nanogenerator for Highly Efficient Mechanical Energy Harvesting. (19th April 2021) - Hajra, Sugato; Sahu, Manisha; Padhan, Aneeta Manjari; Lee, In Sang; Yi, Dong Kee; Alagarsamy, Perumal; Nanda, Sitansu Sekhar; Kim, Hoe Joon
Abstract: The naturally available cyclodextrin has opened up a wide range of research avenues because of its superior characteristics such as being non‐toxic, biocompatible, and edible. The cyclodextrin is the green multifunctional material that can add to the triboelectric series and extend its self‐powered applications. The ultrasonic synthesized cyclodextrin metal–organic framework (CD‐MOF) designed using sodium as a metal ion and cyclodextrin as a ligand for the triboelectric nanogenerator is reported. The various detailed characterizations of the CD‐MOFs give an insight into the properties of the synthesized material. The Kelvin probe force microscopy suggests three types of CD‐MOFs, exhibiting a positive potential. As per the surface potential, the output of the various CD‐MOF based TENG is varied as alpha CD MOF/Teflon > gamma CD‐MOF/Teflon > beta CD‐MOF/Teflon. The alpha CD MOF/Teflon TENG produces an electrical output of 152 V, 1.2 μA, and 14.3 nC, respectively. The fabricated device output is utilized for powering numerous low‐power electronics through a capacitor and bridge rectifier circuit. The multiunit Z‐shaped TENG device is attached to various surfaces such as the shoe heel and the backside of the school bag, and the corresponding energy harvesting response is demonstrated. Abstract : The cyclodextrin (alpha, beta and gamma) metal organic framework helps to extend the triboelectric series and can be utilized for several applications. The triboelectric nanogenerator, with its vertical contact and separation operating mode, is used to effectively harvest biomechanical energy from various exercises, daily activities, and also from a schoolbag that is used by many students into useful electrical energy.